The Influence of Organizational Commitment and Leadership on Organizational Performance Mediated by Organizational Culture in the Context of Realizing Integrity Zone (IZ) Development in the Government Environment of Barito Selatan Regency - Ernawati; Samsuri, Eddy Raya; Kadir, Abdul (Archives of Business Research, 2024)
This research aimed to determine the influence of organizational commitment and leadership on organizational performance is mediated by organizational culture. Respondents are head of development regency of South Barito of 31 people. The result of this research indicated direct influences are (1) organizational commitment have positive correlation and significant influence to organizational culture; (2) leadership have positive correlation and significant influence to organizational culture; (3) organizational commitment have positive correlation and significant influence to organizational performance; (4) leadership have positive correlation and significant influence to organizational performance; (5) organizational culture have positive correlation and significant influence to organizational performance. Meanwhile undirect influences are : (1) organizational commitment significant influence to organizational performance is mediated by organizational culture; (2)organizational culture doesn’t mediate the influence of leadership on organizational performance, in order to realize.